Soil and Rice Responses to Phosphate Fertilizer in Two Contrasting Seasons on Acid Sulfate Soil. Issue 6 (26th March 2017) - Nguyen, De Ngoc; Nguyen, Truc Thanh; Tran, Quy Ngoc; Macdonald, Ben; To, Tuong Phuc; Tran, Dung Van; Nguyen, Qui Van
ABSTRACT: Acid sulfate soils (ASS) are characterized by low pH, aluminum (Al), and iron (Fe) toxicity and are typically deficient in phosphate (PO4 ). The application of phosphorus (P) fertilizer could help reduce the level of exchangeable Al and Fe, thereby improving the rice growth and yield. Five levels of P (0, 20, 40, 60 and 80 kg phosphorus pentoxide (P2 O5 )/ha) were tested with rice varieties MTL560 in the wet season and MTL480 in the dry season. The optimum rate of P was 60 kg P2 O5 /ha for rice in the dry season and 80 kg P2 O5 /ha in the wet season. Soil testing showed at the start of the season that there was sufficient P in the soil. At the end of the season there was a reduction in soil Al and Fe in plots that had P rates above 40 kg P2 O5 /ha. It is therefore likely that P application reduced Al and Fe toxicity through precipitation and formation of Al-P and Fe-P compounds, which boasted yield, rather amending a soil P deficiency.